Multisite musculoskeletal pain in adolescence and later mental health disorders: a population-based registry study of Norwegian youth: the NAAHS cohort study - Eckhoff, Christian; Straume, Bjørn; Kvernmo, Siv (BMJ Open, 2017)
Objectives: To examine the association between multisite musculoskeletal pain in adolescence and mental health disorders in young adulthood. Design and setting: Data were obtained from a linkage between the Norwegian Patient Registry (2008 – 2012) and the Norwegian Arctic Adolescent Health Study, a school-based survey conducted among 10th grade students in North Norway (2003 – 2005). Participants: In total, 3987 (68%) of all 5877 invited participants consented to the registry linkage. Outcome measures: Mental healthcare use and disorders from age 18 – 20 to 23 – 25 years (5 years). Methods: Musculoskeletal pain was measured by the number of musculoskeletal pain sites. Multivariable logistic regression was used to explore the association with later mental healthcare use and disorders. Results: Multisite adolescent musculoskeletal pain was significantly associated with an increase in mental healthcare use and mental health disorders in young adulthood. The relationship was stronger for anxiety and mood disorders, in both genders. Overall, the association between musculoskeletal pain and later mental health problems was attenuated after controlling for adolescent psychosocial and mental health problems, not by physical or sedentary activity. This could be due to confounding or mediation. However, when examining different mental health disorders, we found musculoskeletal pain to be significantly associated with anxiety disorders, and showing a strong trend in mood disorders, when adjusted for the adolescent factors. Conclusions: Physicians should be aware that multisite adolescent pain is associated with mental health problems in adolescence, and that these adolescents are at increased risk of mental health disorders in young adulthood. As youth troubled by mental health problems commonly present physical symptoms it is important to examine for psychosocial problems in order to offer early interventions.